The Step Wise Effect of Vessel Ligation Method on Intra and Postoperative Hypoparathyroidism in the Total Thyroidectomy - Gülçin Ercan; Meltem Küçükyılmaz; Hakan Yiğitbaş; Nadir Adnan Hacım; Serhat Meriç; Ramazan Kuşaslan; Yüksel Altınel; Merve Tokoçin; Tülin Saraç; Yeşim Erbil (Bagcilar Medical Bulletin, 2020)

(untitled)
Objective:The aim of this study was to determine the step-wise effects of vascular ligation method on the parathyroid function in intraoperative and early postoperative periods of total thyroidectomy.Method:A total of 54 patients between the ages of 40 and 61 years, who underwent a total thyroidectomy for euthyroid multinodular goiter between June 2019 and December 2019, were included in this study. Thyroid lobes were separated step by step using the clamp-tie technique including an inferior approach, to preserve the parathyroid glands and recurrent laryngeal nerve. All patients underwent the same routine surgical and phlebotomy procedures. Serum parathyroid hormone (PTH) and Calcium (Ca) levels were measured 2 hours before the operation, during the operation while the inferior and superior poles of the right and left lobe were connected, and at the 12th postoperative hour, and all data were analyzed retrospectively.Results:Of the 54 patients undergoing total thyroidectomy, 7 (12.9%) were male and 47 (87.04%) were female. The mean age was 45.65±8.23 years. In terms of PTH measured in the intraoperative period, a statistically significant decrease was found during the vessel ligation of the superior pole of superior lobe, and lobe excision (p<0.05). In the left lobe, an advanced decrease was detected after the vessel ligation of both poles and lobe excision (p<0.001). When the serum levels of Ca were measured in the intraoperative period, there was no significant change during the surgical procedures of the right lobe, whereas there was a significant decrease after the vessel ligation of the left lobe and the lobe excision procedures (p<0.05). There was a statistically significant decrease in serum PTH and Ca levels in the early post-operative period (p<0.05). A significant decrease in PTH levels of patients without hypocalcemia was observed after ligation of the superior pole of the right lobe, whereas in patients with hypocalcemia, this decline started after the removal of the right lobe (p<0.05). After the right lobe and left lobe excision and at the 12th postoperative hour, significant differences were detected in Ca levels between the groups with and without hypocalcemia. In addition, patients with hypocalcemia showed a significant decrease in Ca levels after left lobe excision and at the postoperative 12th hour (p<0.05 and p<0.001, respectively).Conclusion:The step-wise effects of the vessel ligation method on intraoperative and postoperative PTH levels in total thyroidectomy may vary depending on the presence of hypocalcemia without making a significant difference in the risk of early postoperative complications.